2013
DOI: 10.1101/gad.223180.113
|View full text |Cite
|
Sign up to set email alerts
|

RNF4 and PLK1 are required for replication fork collapse in ATR-deficient cells

Abstract: The ATR-CHK1 axis stabilizes stalled replication forks and prevents their collapse into DNA double-strand breaks (DSBs). Here, we show that fork collapse in Atr-deleted cells is mediated through the combined effects the sumo targeted E3-ubiquitin ligase RNF4 and activation of the AURKA-PLK1 pathway. As indicated previously, Atrdeleted cells exhibited a decreased ability to restart DNA replication following fork stalling in comparison with control cells. However, suppression of RNF4, AURKA, or PLK1 returned the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(114 citation statements)
references
References 58 publications
(115 reference statements)
4
106
0
Order By: Relevance
“…The SUMO E3 Ligase Activity of SLX4 Mediates Toxicity in Response to Global Replication Stress Recent studies reported that SLX4 contributes to DSB formation in response to global replication stress (Couch et al, 2013;Fugger et al, 2013;Ragland et al, 2013). Our findings suggested that these effects might correlate with the SIM-and BTB-dependent cytotoxicity induced by high overexpression levels of SLX4 ( Figure 5B).…”
Section: Sumo-related Functions Of Slx4 Are Not Required For Icl Repamentioning
confidence: 50%
See 1 more Smart Citation
“…The SUMO E3 Ligase Activity of SLX4 Mediates Toxicity in Response to Global Replication Stress Recent studies reported that SLX4 contributes to DSB formation in response to global replication stress (Couch et al, 2013;Fugger et al, 2013;Ragland et al, 2013). Our findings suggested that these effects might correlate with the SIM-and BTB-dependent cytotoxicity induced by high overexpression levels of SLX4 ( Figure 5B).…”
Section: Sumo-related Functions Of Slx4 Are Not Required For Icl Repamentioning
confidence: 50%
“…Remarkably, this SLX4-mediated toxicity was abolished when the SIMs or the BTB were mutated ( Figures 6A and S6B), suggesting that SLX4-dependent SUMO E3 ligase activity is toxic in cells facing global replication fork stalling. Low doses of HU combined with ATR checkpoint kinase inhibition (ATRi) result in cell death associated with replication fork collapse, DSB induction, and extensive ssDNA generation at the fork (Couch et al, 2013;Ragland et al, 2013). Depletion of SLX4 also attenuated the synthetic lethality of the double treatment HU+ATRi in the parental FIT 0 cells ( Figure 6B).…”
Section: Sumo-related Functions Of Slx4 Are Not Required For Icl Repamentioning
confidence: 92%
“…RNF4 has also been implicated in the response to DNA damage and facilitates damage-induced HR in human cells (Galanty et al 2012;Yin et al 2012;Ragland et al 2013). Moreover, DSBs in heterochromatin have been shown to move out of heterochromatin for repair in Drosophila and human cells (Chiolo et al 2011;Jakob et al 2011), and DSB repair pathway choice is also influenced by nuclear position in human cells, with end-joining more prevalent at the nuclear lamina, and HR more prevalent at nuclear pores (Lemaitre et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for checkpoint-dependent replisome stabilization comes from both indirect and direct experimental approaches. These data include decreases in the abundance of some replisome components at stalled forks in checkpoint-deficient yeast as measured by ChIP [17, 4951], loss of early PCNA staining patterns in human and fission yeast cells [43, 52], and decreases in the amount of some replisome proteins bound to chromatin in both Xenopus in vitro replication systems and human cells [45, 53, 54]. …”
Section: How Does the Replication Checkpoint Prevent Fork Collapse?mentioning
confidence: 99%